Bird Neighbors : An Introductory Acquaintance with One Hundred and Fifty Birds Commonly Found in the Gardens, Meadows, and Woods About Our Homes - Blanchan, Neltje, 1865-1918; Burroughs, John, 1837-1921 (Salt Lake City, UT : Project Gutenberg, 1999)
"Bird Neighbors" by Neltje Blanchan is a nature guide published in 1897. This groundbreaking work combines scientific classification with vivid color illustrations and accessible prose, reflecting the author's deep enthusiasm for birdlife. Blanchan organizes birds by habitat, size, and color, making identification easier for everyday readers. The book features photographed stuffed birds against natural backgrounds and includes lyrical descriptions of species like the red-winged blackbird. Selling over 250,000 copies, it established Blanchan as the best-selling female nature writer of her era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Bird_Neighbors
Release date is 1999-09-01
Keywords: Birds